Use of digital guides in museum galleries: Determinants of information selection. (April 2016) - Eghbal-Azar, Kira; Merkt, Martin; Bahnmueller, Julia; Schwan, Stephan
Abstract: Mobile guides play an increasingly important role in informal learning settings such as museums and exhibitions, supplementing traditional museum tours offered by human interpreters. In order to identify visitors' strategies of assessing information provided by a digital guide, two studies were conducted in a large exhibition on modern German literature. By unobtrusively observing visitors' behavior in the exhibition, Study 1 demonstrated that users of the digital guide spent about 60% more time in the exhibition and also scrutinized individual exhibits more extensively. In Study 2, we analyzed a large set of more than 100.000 accesses to information on a digital guide provided in the exhibition. Based on these data, we identified a set of factors that shaped the visitors' selection of exhibit information from the mobile guide. In particular, an exhibit's position in the gallery (showcase number, vertical position), its visible features (size, authenticity), and its popularity (hits on Google, being labeled as highlights on an introductory sheet) predicted visitors' tendency to access additional information about an exhibit, whereas an exhibit's color and legibility, as well as whether the exhibit contained writings had no predictive value. Highlights: We analyze the use of a digital guide in an exhibition on German literature. Users of the digital guide spend more time in the exhibition. Exhibits' position in the gallery predicts access to information in the guide. Size and authenticity, but not color and legibility predict access to information. Visitors select information in the digital guide based on exhibits' popularity.